Influence of dimethoxytriphenylamine groups on carbazole-based hole transporting materials for perovskite solar cells. (15th September 2019) - Wang, Yanqing; Chen, Xingze; Shao, Junjie; Pang, Shihao; Xing, Xinlai; Dong, Ziyu; Liu, Shuang; Cui, Zhendong; Deng, Xinlian; Shi, Chengwu
Graphical abstract: Highlights: Four carbazole derivatives were synthesized and utilized as HTMs in PSCs. Number of TPA groups influence on physicochemical properties were investigated. TPA2 C with two TPA units exhibited higher photovoltaic performance than others. Abstract: The synthesis and characterization of a series of hole transporting materials (HTMs) based on carbazole core and dimethoxytriphenylamine (TPA) groups are reported. By modifying the number of TPA components in the HTMs, the influence of the structure of HTMs molecules on the photovoltaic performance of CH3 NH3 PbI3 perovskite solar cells are investigated.TPA2 C, in which two TPA units are incorporated onto the carbazole core, exhibited higher photovoltaic performance thanTPA1 C, TPA3 C andTPA4 C, which contain one, three and four TPAs, respectively. The introduction of TPA group from one to two can improve the device result, however, additional branches introduced to the carbazole core did not led to higher efficiency.